A Literature Survey on Security Issues in Next Gen WSN - Kaur, Beant; Kaur, Ramanjot (International Journal of Computer Sciences and Engineering, 2021)
Next Gen WSN plays an important role in many fields like environment monitoring, transportation security, military, catastrophic area, health, medical, industry so on. However, the most noticeable feature of Next Gen WSN propagates various types of data such as text, image , videos. There are a lot of papers about Next Gen WSN and maximum papers have focused on how to save the energy of WSN. Saving energy in the form of batteries is challenging when integrating security mechanisms. For efficient secure mechanisms we conducted a survey in this paper and tried to find a solution through which we can propose an approach in which secure communication performs with low battery consumption.